Peningkatan Kemampuan Berpikir Kritis Melalui Metode Inkuiri Sosial Pada Mahasiswa PGSD Semester 1 Universitas Flores - Rando, Agnes Remi; Arafat, Siti (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to find out whether there is an influence of increasing the social inquiry model on elementary social studies education courses for students of the PGSD Study Program at the University of Flores. This research method is quasi-experimental. The population in this study was 75 students in the 1st and 2nd semesters of the PGSD Study Program at Flores University and the research sample was 32 students. The experimental class uses a social inquiry model with orientation steps, formulating problems, formulating hypotheses, collecting data, testing hypotheses, and formulating conclusions. Use of data using tests. Data analysis used the independent t test. The results of the research show that the social inquiry learning model has an influence on the learning of elementary social studies subjects in students of the PGSD Study Program at the University of Flores, with a calculated value of -26.455 with a significance level of 0.05 and df = n-2 = (42-2) = 40, significance 0.000 < 0.05 then Hodi is rejected and Ha is accepted.